Metallacarboranes as a tool for enhancing the activity of therapeutic peptides. Issue 1 (12th August 2019) - Fink, Krzysztof; Boratyński, Janusz; Paprocka, Maria; Goszczyński, Tomasz M.
Abstract: Metallacarboranes are anionic boron clusters with high affinity to serum albumin, ability to cross biological membranes, and no apparent toxicity in vitro and in vivo . Thus, conjugation with cobalt bis(1, 2‐dicarbollide), [COSAN] −, ([3, 3′‐Co(1, 2‐C2 B9 H11 )2 ] − ) may improve the properties of therapeutic peptides or proteins at both molecular and systemic levels. Here, we conjugated [COSAN] − with the therapeutic peptide thymosin β4 (Tβ4), which has a pleiotropic activity that results in enhanced healing and regeneration of injured tissues. Using fluorescence quenching of human serum albumin and surface plasmon resonance techniques, we showed that the conjugates have a high affinity to human serum albumin. Using an in vitro wound closure assay, we showed that conjugation with [COSAN] − enhances the activity of Tβ4 toward fibroblasts (MSU1.1 cell line). These results indicate an application of metallacarboranes in the development of analogs of various therapeutic peptides/proteins with superior pharmacological properties. Abstract : Here, we conjugated [COSAN] − with the therapeutic peptide thymosin β4 (Tβ4), which has a pleiotropic activity that results in enhanced healing and regeneration of injured tissues. Using fluorescence quenching of human serum albumin (HSA) and surface plasmon resonance (SPR) techniques, we showed that the conjugates have a high affinity to HSA. Using an in vitro wound closure assay, we showed that conjugation with [COSAN] − enhances the activity of Tβ4 toward fibroblasts (MSU1.1 cell line).